KAJIAN SOSIO-LEGAL TERHADAP PENGARUH TRADISI LOKAL PADA PELAKSANAAN HUKUM WARIS ISLAM DI INDONESIA - Panji Wardana, Faris; Anam, Misbahul; Yusuf Hasanudin, Muhamad; Sembara, Wahyu; Fitriana Devi, Yanita; Mul Erowati, Eti (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
This study examines the influence of local traditions on the implementation of Islamic inheritance law in Indonesia, focusing on the discrepancies between customary law and sharia law. The main issue lies in inheritance practices that often disregard the faraidh provisions, as seen in the Minangkabau and Aceh communities. The study aims to analyze the dynamics of Islamic inheritance law in Indonesia's pluralistic context. A qualitative approach with case studies was employed. The findings indicate that while efforts to integrate customary law and Islam exist, substantive injustices still need to be addressed. The study recommends harmonizing sharia law with local traditions.